Financiamento da educação do campo na Amazônia paraense: uma análise nos investimentos do Ministério da Educação no estado do Pará - GAMA, Sônia Maria Fonseca (2008)
The purpose of the research is searching the financial public politics for education in the Para State implemented by the Brazilian Ministry of Education from 2003 to 2006, trying to make clear if this public politics offered conditions of developing in the rural area education in Para State, considering the region context. The relevance of this research is due to the fact that the federal and state governments plan the focus of the education in the rural area is a little referred by researchers of the education and the movement for the rural area education is strengthen , however with not enough discussion about the financial plan. The researches accomplished by the quantitative investigation, without considering the quantitative dimension were used the following instruments to collect the data: bibliographic research, documental research with emphasis in the Brazilian laws: field research with interviews in the following institutions: MEC, Secad, Seduc, Undime, INEP and organizations that compound the FPEC. The analysis show that in the space of the rural area of the Amazon of Para, this component of the public politic the financing was and inductor axis and able to direct educational politics through public editals that incentive and make available the resources at the same time that they determinate where they must be used the resources, showing this way, the politics in the rural area education. The analysis still indicate that the government of Luis Inácio Lula da Silva gave visibility to the education of the rural area in this reality and also gave the promotion of reforms of the organization of the movements for the education through Rural Area Education Forum.